The Effects of Different Classes of Antihypertensive Drugs on Patients with COVID-19 and Hypertension: A Mini-Review - Farnoosh Nozari; Nasrin Hamidizadeh (International Journal of Hypertension)
Hypertension is a major risk factor for cardiovascular disease. Previous studies showed that patients with hypertension are at an increased risk of developing severe COVID-19 infection. Therefore, proper blood pressure control in hypertensive patients with COVID-19 is of great importance. In this review, we discussed the effects of different classes of antihypertensive drugs on patients with hypertension and COVID-19.